ART in Europe, 2014: results generated from European registries by ESHRE†: The European IVF-monitoring Consortium (EIM)‡ for the European Society of Human Reproduction and Embryology (ESHRE). Issue 9 (19th July 2018) - De Geyter, Ch; Calhaz-Jorge, C; Kupka, M S; Wyns, C; Mocanu, E; Motrenko, T; Scaravelli, G; Smeenk, J; Vidakovic, S; Goossens, V; ,
Abstract: STUDY QUESTION: What are the European trends and developments in ART and IUI in 2014 as compared to previous years? SUMMARY ANSWER: The 18th ESHRE report on ART shows a continuing expansion of both treatment numbers in Europe and more variability in treatment modalities resulting in a rising contribution to the birth rates in most participating countries. WHAT IS KNOWN ALREADY: Since 1997, ART data generated by national registries have been collected, analysed by the European IVF-monitoring (EIM) Consortium and reported in 17 manuscripts published in Human Reproduction . STUDY DESIGN, SIZE, DURATION: Continuous collection of European data by the EIM for ESHRE. The data for treatments performed in 2014 between 1 January and 31 December in 39 European countries were provided by national registries or on a voluntary basis by clinics or professional societies. PARTICIPANTS/MATERIALS, SETTING, METHODS: From 39 countries and 1279 institutions offering ART services, a total of 776 556 treatment cycles, involving 146 148 with IVF, 362 285 with ICSI, 192 027 with frozen embryo replacement (FER), 15 894 with PGT, 56 516 with egg donation (ED), 292 with IVM and 3404 with frozen oocyte replacement (FOR) were reported. European data on IUI using husband/partner's semen (IUI-H) and donor semen (IUI-D) were reported from 1364 institutions offering IUI in 26 countries and 21 countries, respectively. A total of 120 789 treatments with IUI-H and 49 163 treatments with IUI-D were included. MAIN RESULTS AND THE ROLE OF CHANCE: In 14 countries (17 in 2013), where all institutions contributed to their respective national registers, a total of 291 235 treatment cycles were performed in a population of 208 million inhabitants, corresponding to 1925 cycles per million inhabitants (range: 423–2978 per million inhabitants). After treatment with IVF the clinical pregnancy rates (PR) per aspiration and per transfer were marginally higher in 2014 than in 2013, at 29.9 and 35.8% versus 29.6 and 34.5%, respectively. After treatment with ICSI the PR per aspiration and per transfer were also higher than those achieved in 2013 (28.4 and 35.0% versus 27.8 and 32.9%, respectively). After FER with own embryos the PR continued to rise, from 27.0% in 2013 to 27.6% in 2014. After ED a similar trend was observed with PR reaching 50.3% per fresh transfer (49.8% in 2013) and 48.7% for FOR (46.4% in 2013). The delivery rates (DR) after IUI remained stable at 8.5% after IUI-H (8.6% in 2013) and at 11.6% after IUI-D (11.1% in 2013). In IVF and ICSI together, 1, 2, 3 and ≥4 embryos were transferred in 34.9, 54.5, 9.9 and in 0.7% of all treatments, respectively (corresponding to 31.4%, 56.3, 11.5% and 1% in 2013). This evolution in embryo transfer strategy in both IVF and ICSI resulted in a singleton, twin and triplet DR of 82.5, 17.0 and 0.5%, respectively (compared to 82.0, 17.5 and 0.5%, respectively, in 2013). Treatments with FER in 2014 resulted in a twin and triplet DR of 12.4 and 0.3%, respectively (versus 12.5 and 0.3% in 2013). Twin and triplet DR after IUI were 9.5 and 0.3%, respectively, after IUI-H (in 2013:9.5 and 0.6%) and 7.7 and 0.3% after IUI-D (in 2013: 7.5 and 0.3%). LIMITATION, REASONS FOR CAUTION: The method of data collection and reporting varies among European countries. The EIM receives aggregated data from various countries with variable levels of completeness. Registries from a number of countries have failed to provide adequate data about the number of initiated cycles and deliveries. As long as incomplete data are provided, the results should be interpreted with caution. WIDER IMPLICATIONS OF THE FINDINGS: The 18th ESHRE report on ART shows a continuing expansion of treatment numbers in Europe. The number of treatments reported, the variability in treatment modalities and the rising contribution to the birth rates in most participating countries point towards the increasing impact of ART on reproduction in Europe. Being the largest data collection on ART, the report gives detailed information about ongoing developments in the field. STUDY FUNDING/COMPETING INTEREST(S): The study has no external funding and all costs are covered by ESHRE. There are no competing interests.